Buzzers, Bots, and Brands: Ethical Analysis of Manipulative Technology in Digital PR Practices - Yenny; Muhammad Yus Firdaus; Siska Armawati Sufa; Feliza Zubair; Dedi Setyawan (Faculty of Law, Universitas Pekalongan, 2023)
This study examines the use of buzzers and bots in digital public relations (PR) strategies for Indonesian e-commerce, with a focus on the Shopee competition. The background of the study highlights the shift in PR communication from traditional media to algorithm-based practices that are often manipulative. The main issues are how these practices are carried out, their impact on consumer perceptions, and the ethical dilemmas that arise. The objectives of this study are to analyze buzzer-bot practices in digital PR, examine the ethical perceptions of stakeholders, and identify the boundaries between legitimate communication and manipulative campaigns. The methodology adopts a qualitative constructivist employing techniques such as case studies, interviews, netnography, and document analysis. The results indicate that buzzers and bots are effective in increasing visibility but lead to trust crises, ethical degradation, and reputational risks. The conclusions emphasize the need for regulation, transparency, and sustainable ethical communication strategies.